2023
DOI: 10.3390/biomedicines11092404
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Platelet-Rich Plasma for Low Back Pain

Edilson Silva Machado,
Fabiano Pasqualotto Soares,
Ernani Vianna de Abreu
et al.

Abstract: Background: Low back pain (LBP) has a high economic burden and is strongly related to the degenerative process of the spine, especially in the intervertebral disc and of the facet joints. Numerous treatment modalities have been proposed for the management of LBP, and the use of platelet-rich plasma (PRP) has emerged as an innovative therapeutic option for degenerative disease of the spine. The present study aims to evaluate the efficacy of PRP injections in managing low back pain. Methods: We conducted a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 109 publications
0
1
0
Order By: Relevance
“…Meanwhile, according to reports, platelet-rich plasma injection therapy for lower back pain showed significant improvements in functional outcomes, pain relief, and patient satisfaction compared to placebo (intradiscal contrast agent). It is worth noting that patients who receive platelet-rich plasma injections can still alleviate pain and improve function even after several years of injection, while some surgical patients experience recurrent symptoms and are considered to have failed treatment ( Machado et al, 2023 ).…”
Section: Therapeutic Factorsmentioning
confidence: 99%
“…Meanwhile, according to reports, platelet-rich plasma injection therapy for lower back pain showed significant improvements in functional outcomes, pain relief, and patient satisfaction compared to placebo (intradiscal contrast agent). It is worth noting that patients who receive platelet-rich plasma injections can still alleviate pain and improve function even after several years of injection, while some surgical patients experience recurrent symptoms and are considered to have failed treatment ( Machado et al, 2023 ).…”
Section: Therapeutic Factorsmentioning
confidence: 99%
“…Furthermore, a decrease was observed in the Oswestry Disability Index at the 24-week point. The quality of the evidence recommending PRP therapy for LBP has been graded as level II by Machado ES et al [ 1 ]. Centeno C et al's study demonstrated that platelet lysate epidural injections have been promised as a treatment for lumbar radicular pain.…”
Section: Reviewmentioning
confidence: 99%
“…Musculoskeletal disorders are a major cause of disability and a substantial financial burden on society [ 1 ]. This illness is more expensive than several other diseases when it comes to both direct as well as indirect costs like reduced productivity and retirement at an early stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degenerative processes of the spine not only include OA of the facet joints but also alterations of the intervertebral discs [10][11][12]. In the early phases of disc degeneration a balance shift of anabolic and catabolic activity of extracellular matrix molecules and chondrocytes occurs, which also involves the presence of pro-inflammatory cytokines, including IL-1, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12, IL-15, IL-17, interferon-γ and TNFα [13,14].…”
Section: Introductionmentioning
confidence: 99%